(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Grigaliūnienė, Vėlavičienė, Šulga, and Keblys (2007) have revealed that meaningful relationships with teachers are influenced by positive attitudes towards them with a good emotional atmosphere in the classroom and a positive microclimate between pupils and teachers. Many scientists point out that education in sports activities positively impacts the development of adolescents’ communication and collaboration with peers and adults, adequate self-evaluation and other positive personality characteristics (Kremer-Sadlik & Kim, 2007; Ream & Rumberger, 2008). Research aim was to determine the evaluation of educational school environment and academic self-evaluation of 11–15-year-old adolescent athletes and non-athletes. Methods. The research was conducted in 2015. We questioned 209 adolescents, aged 11–15 years. In order to determine adolescents’ attitudes towards school educational environment, the survey included the following scales: “Teachers’ help for pupils”; “Support of classmates”; “Positive relationship between adolescents and school”; “Attitude towards socioeducational school environment”; “Loneliness at school”, and “Academic self-evaluation”. Results. The survey revealed that boys’ attitudes to socioeducational school environment resulted to be better than that of girls (p < .05) and that younger adolescents felt more help from the teachers at school than older adolescents (p < .05), but they also pointed out that they experienced a stronger sense of loneliness at school (p < .05). More positive relationship was revealed between adolescent athletes and school (p < .05), but adolescent non- athletes had a better attitude to socioeducational school environment. Conclusion. It was found that although adolescent non-athletes had a better approach to socioeducational school environment, their peer reported having a better link with school. Keywords: attitude, adolescent athletes, adolescent non-athletes, feeling at school, sports activity.